Retrieved but not transplanted kidneys: how to limit the losses? A retrospective national study. (14th September 2021) - Alechinsky, Louise; Abdessater, Maher; Parra, Jerôme; Malaquin, Géraldine; Huot, Olivier; Bastien, Olivier; Barrou, Benoit; Drouin, Sarah J.
Summary: Despite the organ shortage, a significant number of deceased donor kidneys are retrieved but not transplanted (RNTK). This study aims to describe and analyze the main causes of potential grafts discard and to propose adequate solutions. We collected data from the Cristal database of the French Biomedicine Agency about RNTK over one year. Expert opinion was taken from urologists with extensive expertise in renal transplantation. They retrospectively analyzed each record to assess the appropriateness of each graft refusal and subsequent kidney discard. Of 252 kidneys were retrieved but not transplanted in France over one year. The main reasons for discard were vascular abnormalities in 43.7% ( n  = 110), suspicion of malignant tumor in 18.7% ( n  = 47), and severe histological lesions on preimplantation biopsy in 12.3% ( n  = 31). The reason for kidney refusal was undetermined in 4.8% ( n  = 12). Iatrogenic lesions were responsible for 26.2% ( n  = 66). Overall, 46.0% ( n  = 16) and 25.0% ( n  = 63) of the grafts were, respectively, properly and improperly denied, and the analysis was not possible in 29.0% ( n  = 73). In total, 36.9% of RNTK could have been transplanted. Reduction of iatrogenic lesions, improvement of microsurgical repair skills, and proper histological examination are necessary to reduce the number of RNTK. A prospective study applying the proposed principles is undoubtedly essential to complete this work.